Analysis of Lipid Profile and Body Mass Index in a Population of Type 2 Diabetes Mellitus Patients in First Level Health Facilities Malang - Putri, Ghinantia Athaya; Bramantya, Rinadhi Reza (Clinical and Research Journal in Internal Medicine, 2026)
Background: Abnormal lipid profiles and body mass index (BMI) has a role in the risk of complications of DM. Aim: This research aimed to describe the lipid profile and BMI characteristics of type 2 DM patients. Methods: Cross-sectional observational study with a retrospective approach used secondary data from Chronic Disease Management Program (Prolanis) patients at First Level Health Facilities (FKTP) in Malang City and it through univariate and bivariate analysis. Results: From univariate analysis, most of patients had total cholesterol in the desired category, triglycerides in the normal category, very high category in LDL, high category in HDL, and obese II category in BMI. Meanwhile, from bivariate analysis, there was a significant relationship between sex and HbA1c on LDL, HDL, and BMI, and there was no significant relationship between age and LDL, HDL, and BMI. Conclusion: Therefore, close monitoring is needed regarding the patient's lipid profile and BMI because they are associated with high risk factors for complications. Keywords: diabetes mellitus, lipid profile, body mass index